An Analysis of the Effect of Pharmaceutical Patent Laws on Access to Medical Care - Agbasi, Maureen Ngozi (ABUAD Law Journal, 2019)
Most developing countries have their public health goals compromised by poor access to essential drugs. One of the causes of this has been attributed to strict patent law regimes. This challenge is acute in developing countries because less than 10 percent of drugs are patented. Developing countries are also handicapped by inadequate access to research facilities and the technological know-how needed for local production with regard to pharmaceutical. This essay is concerned with setting out guidelines for acceptable patents in such a way that public health is not compromised. This work finds that there is need to determine the effectiveness and efficiency of the laws laid down by local and international statues, and whether or not such laws in place are sufficient. The need to distinguish patent protection for both processes and products is also highlighted. This is monumental as process patents provide only protection in respect of the technology and methods of manufacture.